1990
DOI: 10.1111/j.1540-8191.1990.tb00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Development of Intraoperative Left Ventricular Outflow Obstruction: Differential and Mechanism. An Intraoperative Two-Dimensional Echocardiographic Study

Abstract: Systolic anterior motion (SAM) of the mitral valve, once considered to be pathognomonic of hypertrophic cardiomyopathy, has been reported in the absence of asymmetric septal hypertrophy. Of the 1,000 open heart operations performed with intraoperative two-dimensional epicardial echocardiography monitoring, four patients developed intraoperative dynamic left ventricular outflow obstruction associated with systolic anterior motion of the mitral valve that was not present preoperatively: three cases of mitral val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…At a later date, the same group clinically confirmed this by reporting such rings to be a determinant for depressed ventricular function 14 , and supporting the use of malleable rings in carriers of a rheumatic valve pathology with reduced annular contractility, as occurred in 87.6% of the presently studied cases. Furthermore, the rigid ring may also cause the obstruction of the left ventricular outflow tract observed in 4.5 to 10% of the cases [15][16][17][18] , a fact not observed in annuloplasty with completely flexible rings 14,31 or with flexible posterior rings 26,28,29 , results of the present study included.…”
Section: Arq Bras Cardiolmentioning
confidence: 62%
See 1 more Smart Citation
“…At a later date, the same group clinically confirmed this by reporting such rings to be a determinant for depressed ventricular function 14 , and supporting the use of malleable rings in carriers of a rheumatic valve pathology with reduced annular contractility, as occurred in 87.6% of the presently studied cases. Furthermore, the rigid ring may also cause the obstruction of the left ventricular outflow tract observed in 4.5 to 10% of the cases [15][16][17][18] , a fact not observed in annuloplasty with completely flexible rings 14,31 or with flexible posterior rings 26,28,29 , results of the present study included.…”
Section: Arq Bras Cardiolmentioning
confidence: 62%
“…These techniques started to be used together with annuloplasty for recovery of valve function 7,12 . Accumulated experience and new concepts about the physiology of the mitral valve apparatus showed the limitations of this technique, such as fixation of the contractile annulus 13,14 and eventual obstruction of left ventricle outflow [15][16][17][18][19] .…”
mentioning
confidence: 99%
“…Additionally, other conditions such as dehydration, sepsis, vasodilatation, or mitral valve repair have been associated with LVOT obstruction [4,5]. Martinez-Useros et al [6] once reported the case of a patient who had a severe fixed stenotic lesion in the left anterior descending coronary artery that led to dynamic obstruction of the LVOT.…”
Section: Discussionmentioning
confidence: 98%
“…Of the 316 surviving patients, 42 (Fig 3A). Hazard function for mitral structural deterioration is shown in Fig 3B. Thromboembolism Thirty-eight thromboembolic events occurred in this series, 12 peripheral and 26 central (15 transient, 10 with permanent neurologic impairment, and 1 patient died).…”
Section: Follow-upmentioning
confidence: 99%